Cytotoxic effect of imatinib on the normal myeloid and cancer cells of patients with chronic myelogenous leukemia - Al -Jawad, Faruk H. (Iraqi Journal of Cancer and Medical Genetics, 2016)
Background: Chronic myelogenous leukemia( CML) is a type of leukemia in about 20 % of all types of leukemia. It is a malignant clonal, myeloproliferative disorders of the pluripotent hematopoietic stem cells. Aim of study:The present study was aimed to determine in vitro the cytotoxic effect of imatinib on normal myeloid stem cells and leukemic myeloid cells of patients with chronic myelogenous leukemia. Materials and methods: Imatinib was prepared by serial dilution in concentrations (250, 125, 62.5, 31.25, 15.625,7.8125 µg/ ml ), it was added to the cells culture. Using MTT assay. Results: The results show the cytotoxic effect (inhibition rate of growth) of imatinib was in dose and time dependent.There were significant differences between concentrations and time exposure (24,48,72 hr). The highest inhibition rate on the leukemic cells was 89.907% in concentration 250µg/ml and the lowest inhibition was 43.918 % in concentration 7.8125 µg/ml for exposure time 72hr While the highest inhibition rate on the normal myeloid cells was 34.621 % in concentration 250µg/ml and the lowest inhibition was 14.588 % in concentration 7.8125 µg/ml for exposure time 72hr. Conclusions: imatinib has a highly inhibited growth for the leukemic myeloid stem cells and less inhibited for the normal cells.This is a guide for choosing any drug with high cytotoxic effect on the leukemic cells and less cytotoxic effect on the normal cells.